Decision Support System for Supplier Selection Using TOPSIS Method - Aisyah, Siti Nur; Gunawan, Vera Silvia; El-Sayed, Ahmed Hassan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2024)
Supplier selection is a strategic decision that significantly influences organizational performance, cost efficiency, and supply chain sustainability. The increasing complexity of supply chains requires decision makers to evaluate suppliers based on multiple, often conflicting criteria. This study aims to develop a decision support system (DSS) for supplier selection using the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. A case study was conducted in a manufacturing company in Indonesia involving five alternative suppliers evaluated against six criteria, including cost, quality, delivery reliability, flexibility, service level, and environmental performance. Data were collected through expert judgment and company procurement records. The TOPSIS method was applied to normalize decision matrices, determine ideal solutions, and calculate preference values for each supplier. The results indicate that TOPSIS effectively ranks suppliers by considering both the closest distance to the ideal solution and the farthest distance from the negative ideal solution. The DSS developed in this study provides a transparent, systematic, and practical tool to support managerial decision-making in supplier selection. The findings confirm that TOPSIS-based DSS can improve objectivity, consistency, and efficiency in procurement decisions. This study contributes to the growing literature on multi-criteria decision-making in supply chain management and offers practical implications for organizations seeking to enhance supplier evaluation processes.